Anisotropic and temperature dependent mechanical properties of carbon honeycomb. (21st May 2019) - Qin, Qin; An, Haojie; He, Chenwei; Xie, Lu; Peng, Qing
Abstract: Carbon honeycomb (CHC) is a newly synthesized carbon allotropy with promising applications in many fields of science and engineering. In this work, we investigate the mechanical properties of CHC with focus on the anisotropicity in terms of the tilt angle θ in zigzag-armchair (x-y) plane using molecular dynamics simulations. Results show that the tensile strength of CHC ranges from 15.0 to 23.7 GPa at room temperature, which is lower than that of graphene due to the weakness on the junction. Meanwhile, except in the armchair direction, the strength of CHC reduces as the stretching direction moves away from the zigzag direction, similar to that of graphene, while the Young's modulus decreases with respect to tilt angle, opposite to that of graphene. Increasing the temperature will weaken CHC by reducing the strength, there is only a 16% reduction in the minimum strength in the x-y plane as the temperature increases from 100 to 900 K. In addition, the crack occurs first in cell axis direction then in the x-y plane, different from graphene which appears along the zigzag direction only.